Narcissism and suicide in Shakespeare and his contemporaries - Langley, Eric Francis (Oxford : Oxford University Press, 2009)
Through close analysis of Shakespearean texts and discussion of Renaissance revisions of Ovid, this book illustrates how the seemingly extreme figures of the narcissist and self-slaughterer are indicative of early-modern attitudes to interiority.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Shakespeare, William, -- 1564-1616 -- Criticism and interpretation; Shakespeare, William, -- 1564-1616 -- Friends and associates; Narcissism in literature; Suicide in literature; English drama -- Early modern and Elizabethan, 1500-1600 -- History and criticism